Efecto de la edad al primer parto sobre parametros productivos en vacas Jersey de Costa Rica - Castillo Badilla, G.=700 1 Salazar Carranza, M.; Murillo Herrera, J.; Romero Zuñiga, J.J.
(Es, En)
Ilus., 36 ref
Keywords: VACA; PRODUCCION LECHERA; LACTANCIA; EDAD; PARTO; COSTA RICA; VACAS JERSEY